Effect of Participation in Performance Pay Systems and Employees’ Satisfaction with Job Conditions - Arman Ismail; Aimi Anuar (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2017)
The aim of this research is to evaluate the association between participation in performance pay systems and employees’ satisfaction with job conditions. A survey method was utilized to collect data from subordinates who serve at disaster management agencies in West Malaysia. The findings of SmartPLS path model analysis display four important outcomes: first, the relationship between participation in pay plans and satisfaction with intrinsic job conditions was not significant. Second, relationship between participation in pay operations and satisfaction with intrinsic job conditions was not significant. Third, the relationship between participation in pay plans and satisfaction with extrinsic job conditions was significance. Finally, the relationship between participation in pay operations and satisfaction with extrinsic job conditions was significance. This finding demonstrates that participation in pay plans and participation in pay operations do not act as important predictors of employees’ satisfaction with intrinsic job conditions. Conversely, participation in pay plans and participation in pay operations do act as important predictors of employees’ satisfaction with extrinsic job conditions. Further, this research delivers discussion, implications and conclusion.